2017
DOI: 10.1021/acs.molpharmaceut.7b00382
|View full text |Cite
|
Sign up to set email alerts
|

A New Method To Identify Physically Stable Concentration of Amorphous Solid Dispersions (I): Case of Flutamide + Kollidon VA64

Abstract: In this paper, a novel approach to determine stable concentration in API-polymer systems is presented. As a model, binary amorphous mixtures flutamide (FL) drug with a copolymer Kollidon VA64 (PVP/VA) have been used. It is worthwhile to note that finding an effective method to achieve this goal is a matter of great importance because physical stability of the amorphous pharmaceuticals is the key issue that is investigated worldwide. Due to the fact that molecular dynamics was found to be the crucial factor aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…These benefits, however, come at a risk. The high internal energy of amorphous solids, which, on the one hand, is the reason for their high solubility, on the other hand, makes amorphous materials thermodynamically unstable [10][11][12][13][14]. Thus, currently, much effort is being made to (i) investigate physical stability of amorphous form of pharmaceuticals [15][16][17], (ii) find effective methods leading to their stabilization [18][19][20], and (iii) discover the molecular mechanisms responsible for the observed recrystallization inhibition [16,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These benefits, however, come at a risk. The high internal energy of amorphous solids, which, on the one hand, is the reason for their high solubility, on the other hand, makes amorphous materials thermodynamically unstable [10][11][12][13][14]. Thus, currently, much effort is being made to (i) investigate physical stability of amorphous form of pharmaceuticals [15][16][17], (ii) find effective methods leading to their stabilization [18][19][20], and (iii) discover the molecular mechanisms responsible for the observed recrystallization inhibition [16,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the change of real parts of the complex dielectric permittivity obtained from broadband dielectric spectroscopy can be used to characterize the crystallization of amorphous formulations to a certain extent 59. , 60. .…”
Section: Physicochemical Characteristics Of Coamorphous Systemsmentioning
confidence: 99%
“…Therefore, we performed the solubility limit studies. It was recently shown that broadband dielectric spectroscopy (BDS) can be successfully utilized to determine the solubility limits of a drug dissolved within the polymer matrix [16,[28][29][30][31][32]. Since the non-isothermal measurements are, without a doubt, significantly less time-consuming than isothermal ones, and at the same time they provide consistent results [16,28,29], we decided to proceed with the protocol proposed in Reference [16].…”
Section: Solubility Limit Studiesmentioning
confidence: 99%